Exploring Clause Complexity: A Detailed Analysis Within a Specific Text - Ikrimah, Ikrimah; Luardini, Maria Arina (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This study investigates the role of clause complexity in students' academic writing, focusing on the application of Systemic Functional Grammar (SFG) symbols to create persuasive and coherent discourse. Employing a qualitative single-case method, the analysis examines a specific text on the dangers of smoking produced by students. The findings showcase the students' effective use of varied clause types and relationships, as well as their ability to present a systematic and logical flow of ideas supported by factual evidence. The results emphasize the importance of mastering multiple elements, such as utilizing diverse clause types and maintaining a strategic narrative flow, for successful academic writing. These insights can serve as valuable information for educators and academic writers alike, offering a deeper understanding of the implications of clause complexity and its role in fostering effective communication in academic writing.